2002
DOI: 10.1046/j.1440-1746.2002.02841.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA for glucocorticoid receptors in peripheral blood mononuclear cells of patients with Crohn's disease

Abstract: The amounts of GRalpha-mRNA and GRbeta-mRNA in the PBMC of the CD patients were lower than those of the healthy subjects. The duration of disease correlated with decreased amounts of GRalpha-mRNA in the PBMC. Furthermore, the clinical significance of the GR-mRNA status in the PBMC remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Although little has been investigated regarding the mechanism(s) of resistance to immunosuppressive drugs in Crohn's disease (CD), a report by Hori et al suggested that the duration of the disease causes a decrease in mRNA for GR alpha in the PBMCs of CD patients [159]. This observation raises the possibility that duration of inflammation in this disorder may result in a decreased number of GR alpha, which could be a cause of relative PBMC-resistance to GCs in CD.…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Although little has been investigated regarding the mechanism(s) of resistance to immunosuppressive drugs in Crohn's disease (CD), a report by Hori et al suggested that the duration of the disease causes a decrease in mRNA for GR alpha in the PBMCs of CD patients [159]. This observation raises the possibility that duration of inflammation in this disorder may result in a decreased number of GR alpha, which could be a cause of relative PBMC-resistance to GCs in CD.…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Exogenously administered glucocorticoid may downregulate mRNA levels of GR (24,25). However, in the present study, this possibility can be excluded as the CHB patients had not received glucocorticoid treatment for >six months prior to blood sampling.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have demonstrated a dysregulation of pro-and anti-inflammatory cytokines in CHB patients and elevated levels of proinflammatory cytokines may inhibit the expression and function of GR, weakening its anti-inflammatory and immunoregulatory effects during a systemic inflammatory response (22,23). Furthermore, the mRNA levels of GRβ were low compared with total GR levels and their effect on the action of GRα is limited, suggesting that concomitant downregulation in the mRNA expression levels of GRα and GRβ in the PBMCs of CHB patients may result in attenuation, rather than enhancement, of glucocorticoid efficacy (24).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have revealed desynchronization of the mammalian peripheral and central clocks under specific conditions such as timeimposed restricted feeding (Damiola et al, 2000;Hara et al, 2001), parenteral nutrition (Miki et al, 2003;Iwanaga et al, 2005) and glucocorticoid injections (Balsalobre et al, 2000b). Notably, transcriptional activation of the Per1 gene requires a functional glucocorticoid receptor, which is expressed in various peripheral tissues including PBMCs, but not in the SCN (Hori et al, 2002;Rai et al, 2004). Thus, altered post-surgical plasma cortisol concentrations should result in a shift of only peripheral clocks in tissues where high levels of the glucocorticoid receptor are expressed.…”
Section: Discussionmentioning
confidence: 99%